Performance of Aggregate in Relation to Polishing Resistance - Sulandari, Eti; Widodo, Slamet; Mayuni, Siti; Lestyowati, Yoke; Falderika, Falderika; Sutarno, Sutarno (Jurnal Fondasi, 2025)
More than 90% of aggregate is used in asphalt mixtures, meaning the type of rock used as aggregate must comply with permitted specifications. Igneous rocks, as one type of rock, are often used in road construction. Aggregates found in various sources indicate that they possess different characteristics. The resistance of aggregates to polishing demonstrates their ability to support better skid resistance. This study aims to determine the polishing resistance of aggregates by comparing two types of aggregates from different sources (aggregate-1 and aggregate-2). The testing method was conducted in a laboratory, referring to the 2018 Bina Marga and British standards. The equipment includes the polishing Stone Machine and the British Pendulum Tester (BPT).The results showed that both aggregates are suitable for asphalt mixture materials. However, the polishing resistance test results for aggregate-2 (28 BPN) were higher than aggregate-1 (26.4 BPN) because the surface texture of aggregate-2 is coarser, with larger pores, making it rougher. Based on the polishing resistance test, aggregate-1 had longer resistance (65.35%) than aggregate-2 (61.74%) because aggregate-1 is harder than aggregate-2; this can also be observed from their property test results.In conclusion, aggregates from different sources have distinct characteristics and polishing resistance.